Respuesta :
Answer:
See answers below
Step-by-step explanation:
11) 13xy² - 21xy² = -8xy²
12) 2a²b - 17a²b = -15a²b
13) b^(6 + 4) = b^10
14) x^(3 + 8) · y^(5 + 10) = (x^11)(y^15)
15) (3 · 5)a^(4 + 3) = 15a^7
Question :
❖ Simplify the following monomials.
Answers :
11. From 13xy², subtract 21xy²
[tex] \tt = 13x {y}^{2} - 21x {y}^{2} \\ = \tt - 8x {y}^{2} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \\ \\ [/tex]
12. Subtract 17a²b from 2a²b
[tex] \tt = 2a²b - 17a²b \\ = \tt - 15 {a}^{2} b \: \: \: \: \: \: \: \: \: \: \\ \\ \\ [/tex]
Question :
❖ Use the product rule to simplify the following monomials.
Answers :
13. b⁶ • b⁴
[tex] \tt = b⁶ . b⁴ \\ = \tt {b}^{6 + 4} \\ \tt = {b}^{10} \\ \\ \\ [/tex]
14. (x³y⁵)(x⁸y¹⁰)
[tex] \tt = (x³y⁵)(x⁸y¹⁰) \\ \tt = {x}^{(3 + 8)} . {y}^{(8+ 10)} \\ \tt = {x}^{11} {y}^{18} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \\ \\ \\ [/tex]
15. 3a⁴ • 5a³
[tex] \tt = 3a⁴ \times 5a³ \: \: \: \: \: \: \: \: \: \\ \tt = (3 \times 5) {a}^{(4 + 3)} \\ \tt = 15 {a}^{7} \: \: \: \: \: \: \: \: \: \: \: \: \\ \\ \\ [/tex]
Hope it helps you! :)